Targets of glass regulation in the Drosophila eye disc. - Treisman, J.E.; Rubin, G.M. (Mechanisms of Development, 1996)
The Drosophila glass gene is required for the differentiation and survival of photoreceptors in the compound eye, ocelli and larval photoreceptor organ, glass encodes a zinc finger protein which can activate transcription in cell culture and is likely to act by regulating the expression of other genes. We have shown that it directly or indirectly controls the expression of approximately 25% of all enhancer trap lines expressed in the eye disc. glass gene activity is required to activate 19% of the lines, some of which express beta-galactosidase in photoreceptor subtype-specific patterns, and to repress 6%. The phenotype of eye discs doubly mutant for glass and the homeobox gene rough suggests that glass is required for subtype specification and for recruitment of cells to the ommatidial cluster.